Role of CDK4/6 inhibitors in patients with hormone receptor (HR)-positive, human epidermal receptor-2 negative (HER-2) metastatic breast cancer study protocol for a systematic review, network meta-analysis and cost-effectiveness analysis. Issue 5 (30th May 2022) - Hu, Qiancheng; Kang, Wenli; Wang, Qingfeng; Luo, Ting
Abstract : Introduction: It is currently unclear which cyclin-dependent kinase 4/6 (CDK4/6) inhibitor, combined with endocrine therapy, is the preferred treatment approach in patients with hormone receptor (HR)-positive, human epidermal receptor-2 (HER2) negative metastatic breast cancer. The aim of this study was to evaluate the existing evidence for the comparative efficacy, safety and cost-effectiveness of different CDK4/6 inhibitors for metastatic breast cancer in first-line and second-line settings. Methods and analysis: We will systematically conduct a literature search in Embase, PubMed and the Cochrane Library and additional searches by handsearching citations of previous systematic reviews. We will also screen major conference proceedings (American Society of Clinical Oncology, European Society of Medical Oncology and San Antonio Breast Cancer Symposium). Preliminary scoping searches were conducted in July 2021, but the search will be updated when new trials are available. The primary outcome was progression-free survival. The secondary outcomes were overall survival, objective response rates, grade 3–4 haematological and non-haematological toxicities, quality-adjusted life years and incremental cost-effectiveness ratios. The risk of bias will be assessed by Cochrane risk of bias tools, and the quality of evidence will be assessed by the Grading of Recommendations Assessment, Development and Evaluation. Subgroup analyses and sensitivity analyses will be performed to further confirm our findings. In addition, one-way sensitivity analysis and probabilistic sensitivity analyses will be conducted to determine uncertainty. Ethics and dissemination: This study does not require ethics approval as only secondary data will be collected. The results of our study will provide an overview of the current level of CDK4/6 inhibitors for patients with HR-positive, HER2-negative metastatic breast cancer, and undertake subgroup analyses to explore variables that might affect these effects. The results of this study will be presented at an international clinical conference and published in a peer-reviewed journal. PROSPERO registration number: CRD42021266597.